КОМПЛЕКСНА УЧБОВА ПРОГРАМА БЕЗПЕРЕРВНОЇ ПЕДАГОГІЧНОЇ ОСВІТИ ЯК МОДЕЛЬ ОРГАНІЗАЦІЇ ПРОФЕСІЙНО-ПЕДАГОГІЧНОЇ ПІДГОТОВКИ СТУДЕНТІВ ІНЖЕНЕРНО-ЕКОЛОГІЧНОГО ПРОФІЛЮ (Педагогіка вищої та середньої школи, 2010)
In the article the effective organization model of skilfully pedagogic training of engeneering ecological type students through the adoption of complex educational programme of the continuous pedagogic education is grounded in theory.